Clinical profile and outcome of H1N1 influenza in children during August 2016 to January 2017 at KIMS hospital in Bangalore, Karnataka, India - H. S., Ramya; Reddy, N. Varsha Monica; Shekar, Kavya (International Journal of Contemporary Pediatrics, 2018)
Background: Influenza virus is a common respiratory pathogen. In April 2009, a new strain of Influenza virus A H1N1 was evolved and spread in several countries around the world and caused pandemic. After that the resurgence of H1N1 epidemic occurs almost every year and it has caused significant morbidity and mortality. Author present the clinical profile of suspected cases of swine flu infection among children attending our hospital. Methods: This prospective study was conducted at KIMS hospital among 70 children aged 1month to 17 yrs admitted with pneumonia from August 2016 to January 2017 and who consented for the study were included. Institutional ethical clearance obtained. All cases were classified according to WHO ABC category and PRESS (Pediatric Respiratory Severity Score) was applied. Outcome of patients were calculated based on requirement for PICU care, ventilation and PRESS score 4-5. Suspected high risk cases, category B2, and category C cases were started on antiviral Oseltamivir and throat swabs were sent for detection of H1N1 by rRT-PCR. Results: Out of 70 pneumonia cases 44 cases improved with antibiotics and supportive therapy, 26 cases who belonged to category B2 and C and PRESS score 4-5 (severe) were screened for H1N1 influenza and 26 cases were started with empirical antiviral drug oseltamivir.10 out of 26 cases (38.4%) were positive for H1N1 influenza. In our study, fever, cough, breathlessness, and chest x-ray abnormalities were the most common clinical features in both suspected and confirmed cases of H1N1 influenza. Out of 10 cases 2 succumbed (20%). Both the cases had prolonged hospital stay. Conclusions: During monsoon, high degree of suspicion is required in patients presenting with fever, cough, cold and hurried breathing with supportive lab investigations and early administration of antiviral drug provides better outcome, reduces the length of hospital stay and mortality.